2010
DOI: 10.1002/uog.7530
|View full text |Cite
|
Sign up to set email alerts
|

Fetal interrupted aortic arch: 2D‐4D echocardiography, associations and outcome

Abstract: Objectives To analyze fetal two-dimensional (2D) echocardiographic characteristics of interrupted aortic arch (IAA) and its different types

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1
11

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 27 publications
3
47
1
11
Order By: Relevance
“…Vogel et al [19] further reported on the diagnostic value of a low aortopulmonary diameter ratio in the absence of a ventricular size discrepancy in the diagnosis of IAA in their cohort, which also occurred in our study group and helped to facilitate the prenatal diagnosis of IAA ( table 1 ). Volpe et al [18] and Vogel et al [19] also describe a pronounced discrepancy in diameter of the great vessels, which also occurred in our study population.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Vogel et al [19] further reported on the diagnostic value of a low aortopulmonary diameter ratio in the absence of a ventricular size discrepancy in the diagnosis of IAA in their cohort, which also occurred in our study group and helped to facilitate the prenatal diagnosis of IAA ( table 1 ). Volpe et al [18] and Vogel et al [19] also describe a pronounced discrepancy in diameter of the great vessels, which also occurred in our study population.…”
Section: Discussionmentioning
confidence: 60%
“…1 ). Volpe et al [18] found a discrepancy between left and right ventricles in some of their cases with IAA but this was probably due to a restrictive VSD or an associated mitral valve anomaly. The diagnosis of VSD is facilitated using color Doppler echocardiography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 We aimed to do Obstetrician study for antenatal fetal cardiac examination as most of the studies that have been done in the field of antenatal detection of fetal congenital heart defects are about the echocardiography which is done by the pediatric cardiologist for the high risk fetuses as the systemic review and meta-analysis of Yifie et al 16 which studied 82 studies of cardiologists for antenatal fetal echocardiogram, while few number of studies were done for the obstetrician antenatal fetal cardiac screening like the study of Luciane et al 17 in Brazil. Also almost all of these studies were done on risky fetuses only.…”
Section: Discussionmentioning
confidence: 99%